Determining Factors that Influence Household Food Insecurity in Uganda: A Case Study of Tororo and Busia Districts - Owino, Abraham Y.; Atuhaire, Leonard K.; Wesonga, Ronald; Nabugoomu, Fabian; Muwanga-Zaake, Elijah S.K. (International Journal of Sciences: Basic and Applied Research, 2014)
Addressing the national food insecurity problem requires an understanding and measurement of food insecurity at micro-level using a wide range of explanatory variables. Measurement of food insecurity is a challenge because it is a multi-faceted latent and continuous phenomenon explained by many variables. This paper examines these variables and applies exploratory factor analysis to identify variables which significantly influence household food insecurity and how they uniquely associate with specific food insecurity factors. Primary data on food availability, access, utilization and coping strategies were collected from 1175 randomly selected rural households in Tororo and Busia Districts of Uganda. Feasibility of exploratory factor analysis was analyzed using Pearson’s correlation coefficient.
Keywords: Food availability; access; utilization; coping strategies; factor analysis